La educación en tiempos del COVID-19: nuevas prácticas docentes, ¿nuevos estudiantes? - Gazzo, María Fernanda (2020)
We are facinganun precedented situation. The COVID-19 pandemic has come to challengeus. Everydaylife has beendis rupted: from the ways we bond, the way wemakeour general acquisitions, the social and family dynamic seven our interaction with in the educational system. Daily teachers and students putall the ir creativity so that the classrooms, now virtual, remain alive. Undoubtedly, the 21st Century has madeus have the greatest challenge: teaching and learning in times of pandemic.